Implementation Of Digital-Based Health Promotion Model On Clean And Healthy Behaviour In Secondary School Adolescents - Putri, Melati (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
This research is motivated by efforts to change community behavior to improve health. The clean and healthy living behavior development program has actually been running for about 15 years, but its success is still far from expectations. This study aims to increase public insight into the importance of clean and healthy living behavior and to improve public health. Researchers have created a digital platform-based education model for the community to better understand and practice the clean and healthy living behavior program in everyday life in a simple way. This application has features of articles and videos of clean and healthy living behavior. The research method uses the research and development method with the ADDIE model which is carried out in five stages, namely (1) Needs Analysis (2) Application Design (3) Application Development (4) Implementation (5) Evaluation. The subjects in this study were 30 people from Bojong Koneng Village, Babakan Madang District, Bogor Regency. Data collection was carried out via Google Form. Data analysis techniques were carried out quantitatively inferentially. It is known that there is an influence of application use so that there is a significant difference between the pretest and posttest scores. It can be concluded that this PHBS application can be used as a means to increase knowledge of clean and healthy living behavior so that the level of public health can be increased.